THE IMPACT OF SOCIAL MEDIA ON ACADEMIC PERFORMANCE AND STUDENT WELL-BEING IN HIGHER EDUCATION - Muratova, Azada Abdullayevna; Khasanova, Yulduz Mukhtor kizi (Innovative Development in Educational Activities, 2024)
This study explores the impact of social media on academic performance and student well-being in higher education through a mixed-methods approach. Findings indicate that social media is widely used for academic purposes, with students recognizing its influence on academic performance, peer connection, and well-being. While social media enhances access to educational resources and contributes to academic achievement, its impact on time management skills and stress levels varies among students. Educators and institutions may need to support students in navigating the benefits and challenges of social media to promote a balanced and productive learning environment.